Applied Interdisciplinarity in Scholar Practitioner Programs Narratives of Social Change (Springer International Publishing, 2018)
This book examines the experiences of the first graduates from The Doctor of Social Sciences (DSocSci) program at Royal Roads University, Canada's first applied research doctorate designed exclusively for working professionals. The program was developed in response to a growing demand nationally and internationally for scholar-practitioners who are leaders in their professional fields and who want to incorporate dedicated research and writing into their professional lives. Contributors describe their unique experiences in framing and conducting research that was outside the boundaries of discipline-based research and that was driven by issues on the ground. .